Epigenetically deregulated microRNA-375 is involved in a positive feedback loop with estrogen receptor alpha in breast cancer cells - De Souza Rocha Simonini, Pedro; Breiling, Achim; Gupta, Nibedita; Malekpour, Mahdi; Youns, Mahmoud; Omranipour, Ramesh; Malekpour, Fatemeh; Volinia, Stefano; Croce, Carlo M.; Najmabadi, Hossein; Diederichs, Sven; Sahin, Özgür; et al. (Cancer research, 2010)
Estrogen receptor α (ERα) upregulation causes abnormal cell proliferation in about two thirds of breast cancers, yet understanding of the underlying mechanisms remains incomplete. Here, we show that high expression of the microRNA miR-375 in ERα-positive breast cell lines is a key driver of their proliferation. miR-375 overexpression was caused by loss of epigenetic marks including H3K9me2 and local DNA hypomethylation, dissociation of the transcriptional repressor CTCF from the miR-375 promoter, and interactions of ERα with regulatory regions of miR-375. Inhibiting miR-375 in ERα-positive MCF-7 cells resulted in reduced ERα activation and cell proliferation. A combination of expression profiling from tumor samples and miRNA target prediction identified RASD1 as a potential miR-375 target. Mechanistic investigations revealed that miR-375 regulates RASD1 by targeting the 3′ untranslated region in RASD1 mRNA. Additionally, we found that RASD1 negatively regulates ERα expression. Our findings define a forward feedback pathway in control of ERα expression, highlighting new strategies to treat ERα-positive invasive breast tumors. Cancer Res; 70(22); 9175-84. ©2010 AACR.
Gesehen am 01.08.2023